1985
DOI: 10.1002/j.1460-2075.1985.tb03774.x
|View full text |Cite
|
Sign up to set email alerts
|

The HBV HBX gene expressed in E. coli is recognised by sera from hepatitis patients.

Abstract: We have cloned the X gene (HBx) and the HBc antigen (HBc Ag) gene of human hepatitis B virus (HBV) in Escherichia coli as fusion products with beta‐galactosidase. Both HBV genes are expressed in E. coli strain CSR 603. Expression is detected by u.v. irradiation of the bacteria, metabolic labelling and electrophoresis of the labelled extracts on SDS‐polyacrylamide gels. The HBc Ag protein produced in bacteria can be recognised by anti‐HBc sera and peptides derived from the protein are also recognised by anti‐HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…Expression of the X gene in HBV-infected livers has been inferred from the preferential conservation of the X sequence within integrated HBV DNA in HCC and cirrhotic livers with HBV infection, [65][66][67][68] the frequent occurrence of X sequence components containing RNA in HCC specimens, 33,34 the emergence of circulating antibodies, [35][36][37][38][39][40][41][42] and the demonstration of a frequent cellular immune response 43 specific to HBx. The detection of HBx has, however, proved to be very difficult, and the reported data are contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the X gene in HBV-infected livers has been inferred from the preferential conservation of the X sequence within integrated HBV DNA in HCC and cirrhotic livers with HBV infection, [65][66][67][68] the frequent occurrence of X sequence components containing RNA in HCC specimens, 33,34 the emergence of circulating antibodies, [35][36][37][38][39][40][41][42] and the demonstration of a frequent cellular immune response 43 specific to HBx. The detection of HBx has, however, proved to be very difficult, and the reported data are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…RNA, containing components of the X region, has been demonstrated by reverse-transcription polymerase chain reaction. 33,34 Circulating antibodies reactive to recombinant HBx, [35][36][37][38][39][40][41][42] and HBx-specific cellular immune response, 43 may be detected in patients with chronic hepatitis B. By means of antibodies against recombinant HBx or its fragments, some immunoreactivity has been demonstrated in HBV-infected livers, 14,39,[44][45][46][47][48][49][50][51] with three polypeptides identified as the HBx antigen in HCC-bearing livers of HBV-infected Chinese patients.…”
mentioning
confidence: 99%
“…The designation X gene/protein originally reflected its unknown function and lack of homology with known proteins. An HBx mRNA has been detected in the livers of WHV-infected woodchucks and in HBV-infected human liver tissue, and antibodies to HBx have been detected in some infected individuals (31,49,66). Studies suggest that the WHV HBx protein (also referred to as WHx) accumulates to 10,000 to 50,000 copies per cell (31).…”
Section: General Features Of Hbxmentioning
confidence: 99%
“…Its genome contains four recognized open reading frames, three of which code for known virion proteins (2). The fourth, called the HBV X gene ( HBx ), is conserved among all mammalian hepadnaviruses and has been shown to be expressed both during viral infection (3)(4)(5) and in HBV-associated hepatocellular carcinoma (6). Recently, it has been shown that the woodchuck hepatitis virus X gene is important for the establishment of viral infection in woodchucks, suggesting that the HBx gene plays an important role in HBV replication in humans (7).…”
Section: Introductionmentioning
confidence: 99%